Natural Resource Management Sector Expectations from Union Budget 2019-20 - Reddy, K Sammi; Reddy, A Amarender; Sharma, K L; Alagusundaram, K (Indian Farming, 2019)
The article analyzed the macro-economic policies and budgetary allocation to natural resource management related schemes in India. The drylands are neglected in investments and policy issues for long. Special emphasis needs to be given to dryland areas and crops in budget especially in the ongoing schemes like Pradhan Mantri Krishi Sinchai Yojana, Pradhan Mantri Fasal Bima Yojana, Rashtriya Krishi Vikas Yojana and NMSA.